2022
DOI: 10.14214/sf.10609
|View full text |Cite
|
Sign up to set email alerts
|

Wooden multi-storey construction market development – systematic literature review within a global scope with insights on the Nordic region

Abstract: Climate change sets high pressures on the construction industry to decrease greenhouse gas emissions. Due to the carbon storage properties and potential to use renewable resources efficiently, wooden multi-storey construction (WMC) is an interesting alternative for the construction industry to enhance sustainable development combined with the aesthetic and well-being benefits of wood perceived among many consumers. For forest industry firms, industrial wood construction is a possibility to seek for business op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 60 publications
2
6
0
Order By: Relevance
“…This finding suggests great sensitivity to change management skills in development of the WMC BE. The findings thus contribute to understanding the critical role of business collaboration in enabling innovation within WMC market development as noted in existing literature (e.g., Nordin et al, 2010;Gosselin et al, 2018;Toppinen et al, 2019;Riggio et al, 2020;Jussila et al, 2022).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…This finding suggests great sensitivity to change management skills in development of the WMC BE. The findings thus contribute to understanding the critical role of business collaboration in enabling innovation within WMC market development as noted in existing literature (e.g., Nordin et al, 2010;Gosselin et al, 2018;Toppinen et al, 2019;Riggio et al, 2020;Jussila et al, 2022).…”
Section: Discussionsupporting
confidence: 61%
“…We note that the objective of this qualitative interview study is not to present generalizable results of the Finnish WMC case or beyond it, but to understand the BE from the value creation perspective in the context of actual projects. Rationale for this study is given by the need to enhance the efficiency and sustainability of the construction sector, and acknowledging the increasing expectations towards the businesses to make changes in the dominating construction practices (O'Neill and Gibbs 2014; Jussila et al, 2022). Due to the limited temporal data and qualitative approach used in the study, it is, however, difficult to assess in any absolute terms the significance of the various business ecosystem participants and their mutual influencing in regard to the development and market diffusion of WMC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, timber buildings have been gaining increasing global attention since some authors, for example, De Araujo et al [23,24], Petruch and Walcher [25], Toivonen et al [26], and Jussila et al [27], have confirmed its up-and-coming market status. Other relevant studies discuss construction supplies [16,[28][29][30], identification of different timber construction techniques [31][32][33][34][35], forecasts of market trends [36][37][38], and evaluations of market potential for specific construction techniques [39][40][41].…”
Section: Timber Construction and The Demand About Its Electronic Marketmentioning
confidence: 99%
“…Replacing emission-intensive raw materials with wood in the construction sector is considered a potential option to decrease embodied GHG emissions [ 34 ]. Wood construction is expected to face positive market prospects, which are at least partly driven by claims of its superior environmental performance (e.g., [ 21 , 32 ]). Wood construction has a long tradition in countries with substantial forest resources and forest industries, such as the Nordic countries.…”
Section: Introductionmentioning
confidence: 99%